2012
DOI: 10.4238/2012.may.18.12
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of a novel splice variant of the complement component 4 (C4A) gene in mastitis-infected dairy cattle

Abstract: ABSTRACT. The complement system helps in the direct lysis of invading pathogens and modulates phagocytic, humoral and cellular immune responses. Complement 4 is a critical component in complement activity and protection against many bacterial pathogens because it is essential to classical and lectin activation pathways. We used reverse transcription and PCR to investigate alternative splicing and expression of the complement component 4 (C4A) gene in Chinese Holstein cattle. The PCR products were cloned and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…The complement system is a primary line of defense against infection . The bovine complement component 4 (C4A) was significantly associated with the susceptibility to intramammary infections by major pathogens . Günther et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complement system is a primary line of defense against infection . The bovine complement component 4 (C4A) was significantly associated with the susceptibility to intramammary infections by major pathogens . Günther et al.…”
Section: Discussionmentioning
confidence: 99%
“…27 The bovine complement component 4 (C4A) was significantly associated with the susceptibility to intramammary infections by major pathogens. 28 Gunther et al reported that mastitis could up-regulate the mRNA abundance of the C4A gene in E. coli-infected udders. 29 In the present study, the C4F gene and protein were down-regulated in the S. agalactiae group.…”
Section: ■ Discussionmentioning
confidence: 99%
“…[ 50 ] observed the SNP (g9788 C>T) where CC genotype was more prevalent than TT among Frieswal crossbreed cattle, and C allele was observed to be favorable for mastitis resistance and may be used as one of the molecular marker. RT-PCR analysis of C4A gene (chromosome 8) could reveal the SNP rs132741478: g.2994A>G in the coding sequence of the ß-chain and is found to be related with mastitis resistance [ 51 ].…”
Section: Immuno-pathogenesismentioning
confidence: 99%
“…The expression of two new transcripts in these tissues and cells were up-regulated in response to mastitis infection. Alternative splicing is an important mechanism to regulate transcription and proteome complexity by producing multiple mRNAs from a single resistance or susceptibility-related gene, like LTF, SLAMF7, CLU, C4a and A2M that are found to be involved in mastitis resistance or susceptibility to mastitis (Huang et al, 2011;Ju et al, 2012;Wang et al, 2012a;Yang et al, 2012;Li et al, 2013). In human, NCF1 gene is accompanied by two almost similar (>99.5%) pseudogenes (NCF1B and NCF1C) which might arise by gene duplication (Görlach et al, 1997).…”
Section: Discussionmentioning
confidence: 99%